Grammatical Structure and Linguistic Features of English Idioms - Kokanova Nursuliu Jenisbay qizi; Askarova Nafisa Avazovna (Web of Journals Publishing, 2023)
In this article, we will discuss the grammatical structure and linguistic features of English idioms and its importance, as well as one of the most difficult topics in the English language.
Keywords: idioms, language learning, expressions, phraseology, phrases, special approach.